Participatory analysis of the sweet cherry sector in Argentinian South Patagonia - Mundet, CA; Córdoba, Diana M.; Álvarez, S.; Cittadini, ED (2014)
Sweet cherry production is a newly developed and promising activity in Argentinian South Patagonia. Together with a rapid increase in area (from 176 ha in 1997 to 635 ha in 2009), problems related to productivity and commercialization have threatened its sustainability. To gain a collective understanding of the complexity of the cherry sector, a participatory approach has been proposed for research. The steps followed and the contribution of this participatory methodology to a better under¬standing of the sector and the possible solutions to overcome un-sustainability are described. The methodology (Participatory Impact Pathways Analysis – PIPA) allowed different stakeholders to make explicit their assumptions and hypotheses about how the project will achieve its desired goals and changes. The first step was a problem tree analysis where participants identified the main problems of the sector and suggested main changes and outcomes as well as the vision expected from the project intervention. The most important constraints described by the different stake-holders’ group were: (a) inappropriate technology use at packinghouses and at farm level (requiring improvement of technology generation and transfer, and funding), (b) low profitability (less than 50% of the fruit is exportable and labour efficiency is low) and (c) commercialization (low prices, exchange rate, absence of contracts and unreliable brokers). The following step consisted of mapping the sector. Network maps were drawn by four groups of stakeholders: (1) packers and members of growers’ organizations, (2) researchers, (3) extension agents and growers and (4) politically important actors. Positive and negative influences and connections between stake¬holders were described. Afterwards, an Outcome Logic Model of the project was constructed showing how project activities and inputs will lead to outputs, which in turn may lead to changes in knowledge, attitudes and skills, which in turn may lead to changes in behavior (outcomes) that over time will have impacts (reduced poverty for example). While implementing the project, reflection spaces were carried out in order to generate a collective process of reflection on the advances of the project (monitoring and evaluation).